From folk art to fine art: changing paradigms in the historiography of Maithil - Neel Rekha (Journal of Art Historiography, 2010)
The paper is a brief survey of the historiography of Maithil painting after independence. Tracing the roots of current perceptions of Maithil art to the 1949 article of W.G. Archer, the paper demonstrates how his interpretations were articulated by Maithil and non-Maithil scholars and promoters of Maithil art to project a regional, caste-based and national identity. It also looks at the ways in which Maithil art got misinterpreted with the arrival of western scholars in Mithila. The paper reviews the recent shifts in the historiography of Maithil painting by examining the emergence of Harijan Madhubani art. It examines how the legacy of colonial interpretations, romanticization of past history and debates on innovation and tradition, have changed the trajectories of the historiography of Maithil painting in the past few decades.